Demographic and Socio-economic Changes in Bangladesh: Evidence from the Population Census in 2022 - Manik, Mehedi Hasan (Formosa Journal of Sustainable Research, 2024)
Bangladesh is a developing country, so demographic and socio-economic characteristics are rapidly changing. The latest household and population census in the country was held in 2022. The study objective is to show the demographic and socio-economic status in Bangladesh based on the census data. Data have been collected from the website of the Bangladesh Bureau of Statistics. Urbanization in the country is growing although 68.34% of the 169.83 million population is living in the rural area. The literacy rate and dependency ratio of the country are 74.66% and 52.64, respectively, while the sex ratio at birth is 98.0. The toilet facilities of 9.38% of people are unhealthy while about 1.0% are living without electricity. The government of Bangladesh should arrange awareness campaigns to improve the use of healthy toilets, and it should allocate more funds in the energy sector to boost the renewable energy sector